Expert reviewsRenal denervation – current evidence and perspectives - Warchoł-Celińska, Ewa; Prejbisz, Aleksander; Florczak, Elżbieta; Kądziela, Jacek; Witkowski, Adam; Januszewicz, Andrzej (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Clinical trials have demonstrated that catheter-based renal denervation (RDN) reduces blood pressure and improves blood pressure control in patients with resistant hypertension. The follow-up data indicate that the blood pressure lowering effect of the procedure may last for up to 36 months. Despite the fact that RDN is a growing and promising technique, still more data from clinical trials are needed to support the long-term safety and persistent efficacy of this approach as compared to the best possible pharmacological treatment. It would also be particularly important to recognize the clinical features of patients who would benefit most from RDN as well as the clinical characteristics of non-responders to the procedure. As renal denervation also reduces whole-body sympathetic nerve activity, the clinical entities characterized by sympathetic nervous system activation – including hypertension coexisting with metabolic abnormalities and/or sleep apnea, chronic kidney disease, heart failure, and arrhythmias – may be potential new indications for the procedure. However, only a few small clinical studies so far have shown the potential benefit of renal denervation in these clinical situations and large clinical trials are needed to prove this concept. Catheter-based RDN is a promising (but also novel) therapeutic approach and further studies should also verify whether it can be considered as a procedure in management of patients not only with resistant hypertension, but also as a tool in the treatment of mild to moderate forms of hypertension.